Análisis de la producción en yacimientos de gas con baja permeabilidad - Guzmán Arévalo, José David (My University, 2012)
Análisis de la producción en yacimientos de gas con baja permeabilidad
Análisis de la producción en yacimientos de gas con baja permeabilidad
Keywords: Análisis de la producción en yacimientos de gas con baja permeabilidad